How Streams of Communication Reproduce and Change Institutional Logics: The Role of Categories - Ocasio, William; Loewenstein, Jeffrey; Nigam, Amit (Academy of Management Review, 2015)
We examine how streams of communication enable the reproduction and change of the underlying principles that constitute institutional logics. While past research has shown that communication provides instantiations of institutional logics, the link between specific instances of communication and the emergence of institutional logics has not been explicitly shown. To remedy this gap, we propose that collections of communicative events distributed throughout organizations and institutional fields can converge on systems of categories so as to yield the meaningful and durable principles that constitute institutional logics. We explore how four analytically distinct communicative functions—coordinating, sensegiving, translating, and theorizing—enable this emergent process of reproduction and change.